Thermal-hydraulic design of natural circulation integrated steam generator using design map. (October 2021) - Kim, Namhyeong; Kim, Hyungmo; Eoh, Jaehyuk; Kim, Moo Hwan; Jo, HangJin
Highlights: A new natural circulation SG concept to prevent SWR, which uses LBE, was proposed. A design parameter evaluation method using the design map was proposed. The design parameter effects for the NCISG were evaluated by the design map. The trend of UA value according to the LBE cold plenum temperature was analyzed. Abstract: A natural circulation integrated steam generator (NCISG) is a new steam generator concept that prevents the sodium-water reaction, which is a major safety issue in sodium heat transfer systems using the water Rankine cycle. To estimate and enhance the heat transfer performance of NCISG according to the design parameters, a design parameter evaluation method using the design map is suggested for the natural circulation system. The design map evaluates the effect of the temperature distribution of the heat transfer system in advance, allowing a simpler evaluation of the design parameters of a natural circulation system. The design map of NCISG is presented, and the effects of the tube diameter and pitch-to-diameter ratio (P/D) on the heat transfer area and natural circulation flow rate were evaluated. The heat transfer area is mostly affected by the tube diameter and the natural circulation flow rate is mostly affected by the P/D. The tendency of the total heat transfer area to be small in a specific natural circulation mass flow rate, regardless of the tube diameter or P/D, was identified and analyzed as a trend of the total UA value according to the natural circulation flow rate and optimal temperature. Finally, the optimal design of the NCISG under the evaluated design variable conditions is presented.